2004
DOI: 10.1529/biophysj.104.050377
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Single Tryptophan Residues to the Fluorescence and Stability of Ribonuclease Sa

Abstract: Ribonuclease Sa (RNase Sa) contains no tryptophan (Trp) residues. We have added single Trp residues to RNase Sa at sites where Trp is found in four other microbial ribonucleases, yielding the following variants of RNase Sa: Y52W, Y55W, T76W, and Y81W. We have determined crystal structures of T76W and Y81W at 1.1 and 1.0 A resolution, respectively. We have studied the fluorescence properties and stabilities of the four variants and compared them to wild-type RNase Sa and the other ribonucleases on which they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…The unusual positive CD band at 235 nm observed for folded RNase Sa has been discussed previously. 54 The CD spectrum of thermally denatured RNase Sa differs substantially from that of the urea denatured protein, as has been observed in studies of other proteins. 55 The CD spectrum of the protein in 8.5M urea is consistent with the presence of substantial amounts of polyproline II (PPII) conformation.…”
Section: Resultsmentioning
confidence: 84%
“…The unusual positive CD band at 235 nm observed for folded RNase Sa has been discussed previously. 54 The CD spectrum of thermally denatured RNase Sa differs substantially from that of the urea denatured protein, as has been observed in studies of other proteins. 55 The CD spectrum of the protein in 8.5M urea is consistent with the presence of substantial amounts of polyproline II (PPII) conformation.…”
Section: Resultsmentioning
confidence: 84%
“…To monitor the folding and unfolding of WT RNase Sa and the charge‐reversal variant, D17R, by fluorescence spectroscopy, a Trp residue was added in place of Tyr 81. The crystal structure of Y81W showed that the Trp is 87% buried, and the variant is 0.4 kcal/mol less stable than WT (Alston et al 2004). For Y81W RNase Sa, there is a 2.5‐fold increase in fluorescence intensity at 319 nm when the protein folds (Alston et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, changes observed in tryptophan fluorescence signal are induced when the indole ring is involved in binding or upon occurrence of conformational changes in the protein, which involve a change in the environment of the tryptophan residue (e.g. protein unfolding) (83). Indeed, CaM-induced MA unfolding leads to exposure of both Trp 16 and Trp 36 rings and is likely to contribute to the observed changes in the fluorescence signal.…”
Section: Discussionmentioning
confidence: 99%